POLA PEMBENTUKAN PADA PERILAKU TOLERANSI BERAGAMA ANAK (Studi Kasus di LKSA Nur Hidayah Kecamatan Laweyan Kota Surakarta) - Fathiana Vellayati; Rahesli Humsona (Universitas Sebelas Maret (UNS), 2020)
This study aims to determine the formation of Nur Hidayah LKSA in fostering religious tolerance in children in the community. The theory used in this study is the social practice of Pierre Bourdieu, the formula of social parktik theory is (habitus + capital) x realm. This research is a type of qualitative research with a case study approach. Data collection techniques used are (1) non-participatory observation techniques, namely data collection through nonverbal observations (2) unstructured interview techniques, asking questions jumping from time to time or from one topic to another topic (Slamet, 2006), (3) documentation study, which documented the results of interviews and then made an interview transcript of the recordings and personal notes during the study. The sampling technique in this study used a purposive sample. Data validity uses source triangulation to compare data. Data analysis techniques consist of three activities that occur simultaneously, namely: data reduction, data presentation, drawing conclusions.This study shows that (1) the concept of habitus can be seen through LKSA Nur Hidayah provides the formation of religious tolerance in children given through studies twice a week besides LKSA Nur Hidayah teaches about religious and social life, (2) social capital undertaken LKSA Nur Hidayah can give birth to an open attitude and accept differences, peace and tolerate the inconveniences of life. That is because between the community and LKSA Nur Hidayah trust each other, running the norms that apply in the community. LKSA Nur Hidayah frees her foster children to make friends with anyone, but still maintains her own faith and is not influenced by others, (3) cultural capital that is realized is the community invites orphanage children to mutual cooperation and children join mutual cooperation with the community, ( 4) Symbolic capital is a palebelan or assessment of others, a pretty good citizen education and has a modern mindset so that tolerance can be created between Nur Hidayah LKSA and the community, (5) economic capital is closely related to finance, the obligation of Nur Hidayah LKSA is to finance foster children's schooling and paying caregivers and holding social services.